Let y be an implicit function of x defined by x 2 x − 2 x x cot y − 1 = 0 .
Find the value of y ′ ( 1 ) , where y ′ denotes the first derivative of y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
However y is not a function of x. There is simply an implicit relation between x and y. Coincidently whether you take pi/2 or minus pi/2, the derivative is the same.
We are Given x 2 x − 2 x x cot y − 1 = 0 ( x x ) 2 − 2 ( x x ) ( cot y ) + cot 2 y − 1 − cot 2 y = 0 ( x x − cot y ) 2 = 1 + cot 2 y x x − cot y = csc y x x = cot y + csc y Taking Derivative w.r.t x both side x x ( 1 + ln x ) = − csc 2 y × y ′ − csc y cot y × y ′ x x ( 1 + ln x ) = − csc y ( csc y + cot y ) y ′ y ′ = − x x csc y x x ( 1 + ln x ) y ′ ( 1 ) = − csc ( y ( 1 ) ) 1 1 ( 1 + ln 1 ) ⟹ − sin ( y ( 1 ) ) From our Original Equation , 1 2 − 2 × 1 1 cot y ( 1 ) − 1 = 0 ⟹ y ( 1 ) = 2 π y ′ ( 1 ) = − sin ( y ( 1 ) ) ⟹ − 1
@Sabhrant Sachan What does mean w.r.t.x in your solution??????????????????????????????????????????????????????????????????????
Problem Loading...
Note Loading...
Set Loading...
x 2 x − 2 x x cot y − 1 1 − 2 cot ( y ( 1 ) ) − 1 ⟹ cot ( y ( 1 ) ) y ( 1 ) = 0 When x = 1 = 0 = 0 = 2 π
Now, we have:
x 2 x − 2 x x cot y − 1 2 ( ln x + 1 ) x 2 x − 2 ( ln x + 1 ) cot y + 2 x x csc 2 y d x d y 2 − 0 + 2 csc 2 2 π y ′ ( 1 ) y ′ ( 1 ) = 0 Differentiate both sides with respect to x = 0 When x = 1 = 0 = − 1